2016
DOI: 10.3389/frobt.2016.00054
|View full text |Cite
|
Sign up to set email alerts
|

Image Classification to Support Emergency Situation Awareness

Abstract: Recent advances in image classification methods, along with the availability of associated tools, have seen their use become widespread in many domains. This paper presents a novel application of current image classification approaches in the area of Emergency Situation Awareness. We discuss image classification based on low-level features as well as methods built on top of pretrained classifiers. The performance of the classifiers is assessed in terms of accuracy along with consideration to computational aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Textual Multi-modal Run 4 (visual) Run 5 (visual) Feng et al [31] 64. 35 Table 5. Evaluation of our proposed approach for the FDSI task in terms of F1 Scores.…”
Section: Methodsmentioning
confidence: 99%
“…Textual Multi-modal Run 4 (visual) Run 5 (visual) Feng et al [31] 64. 35 Table 5. Evaluation of our proposed approach for the FDSI task in terms of F1 Scores.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to Twitter, images shared through social media have also been widely utilized for disaster analysis [5,3,82]. In this regard, the additional information, such as users' tags, geo-location and temporal information, available in the form of meta-data have been proved very effective, both individually and in combination with visual features.…”
Section: Disaster Detection In Images From Social Mediamentioning
confidence: 99%
“…For example, understanding the extent of the infrastructure and utility damage caused by a disaster is one of the core situational awareness tasks listed earlier. Several studies in the literature have already shown that social media images can be analysed for automatic damage assessment in addition to the textual content analysis (Liang, Caverlee, and Mander 2013a;Daly and Thom 2016;Lagerstrom et al 2016;Nguyen et al 2017c). Inspired by these studies, we perform an infrastructural damage assessment task on cleaned social media imagery content.…”
Section: Extracting Useful Informationmentioning
confidence: 99%